CONCEPTUAL FRAMEWORK FOR INFOGEOLOGICAL MODELING OF MILITARY ACTIVITY TERRITORIES - Khrushchov, D.; Chumachenko, S.; Zatserkovnyi, V.; Trofymenko, P.; Splodytel, А. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The purpose of the study is to elaborate framework of infogeological modeling of the military activity territories (using territorial objects in Ukraine) to provide informational support of research and works on the treatment of the geological environment of territories of military activity. The main methodological instrument of informational support of research and works on the treatment of the geological environment of territories of military activity is information modeling. Given the local level of military activity territories, the complex ecological and geological model serves as the primary methodological technique. Methods developed on this paradigm's principles aim to eliminate the consequences of military activity and restore the territories of the military conflicts. Ground research was developed using conceptual models, particularly checking main components of these models that aim at determining the indetermination. To identify the influence of the military activity sources, we used the Leopold Matrix and Sorensen Level Diagram, network diagram, method of the combined analysis of maps, and factor analysis. The evaluation of the spread of factors of military and technogenic load of chemical origin in the functional zones and subzones of the military polygon was carried out based on the complex approach to the ecological evaluation of the contamination of the territories of intensive military and technogenic load using the landscape profiling and imitating modeling taking into account geochemical and hydrometeorological conditions. The analysis of the soils, contaminated with military and technogenic origin substances in the places of functional subzones locations targeted fields of military polygon showed the indicators of concentration of some of the contaminating substances exceed norms 5-20 times. Field research in military polygon showed that contamination of its territory has zonal character and is grouped around local subzones of the military object where military preparation using armaments and military equipment is carried out, being the primary source of factors of military and technogenic load of the geological environment. Prospects for further development of this field lie in developing the integral theory of infogeological modeling of geological environment of military activity territories, oriented at the evaluation of different types of influences and threats.
Keywords: geologic environment; infogeologic modeling; infogeoframe; military polygon